The Principal's Roles in the Development of Merdeka Curriculum at Junior High school - Maizuroh; Cicih Sutarsih (Didaktika: Jurnal Kependidikan, 2025)
This research aims to ascertain the principals' roles in developing the curriculum at SMP Negeri 4 Merangin, especially when the Merdeka Curriculum is used. The principal's roles as a leader includes ensuring that the curriculum is in line with national policy about the needs of students. The roles include curriculum planning, implementation, and evaluation. To provide a detailed picture of how principals assist in each phase of curriculum development, The research method used is qualitative with a case study approach. This study involved the principal, the deputy of curriculum, and teachers. The study highlights the critical role of school principals in the planning and implementation of the Merdeka Curriculum at SMP Negeri 4 Merangin. As educational leaders, principals ensure teachers are equipped with the necessary knowledge, skills, and resources through workshops, training, and collaboration with education offices and school committees. The implementation process is supported by targeted socialization, teacher development programs, and systematic monitoring to align curriculum execution with established plans. Despite overall progress, challenges such as limited teacher readiness and inadequate infrastructure persist. To address these obstacles, principals employ strategies such as organizing regular training sessions, fostering collaboration with other schools, and providing access to additional resources, ensuring a comprehensive and sustainable curriculum implementation.